One-step carbon nanotubes grafting with styrene-co-acrylonitrile by reactive melt blending for electrospinning of conductive reinforced composite membranes. Issue 12 (2nd December 2017) - Vassiljeva, V.; Kirikal, K.-K.; Hietala, S.; Kaljuvee, T.; Mikli, V.; Rähn, M.; Tarasova, E.; Krasnou, I.; Viirsalu, M.; Savest, N.; Plamus, T.; Javed, K.; et al.
ABSTRACT: Aim of this research was to electrospin conductive composite membrane of styrene-co-acrylonitrile (SAN) reinforced with carbon nanotubes (CNTs). To improve electrical conductivity of final membrane ionic liquid (IL) was used. For better dispersion of CNTs in SAN matrix one-step reactive melt blending method for grafting of SAN onto CNTs was developed. Influence of SANm-g-CNTs on solutions properties was studied and compared to solutions with ungrafted CNTs and carboxyl group functionazed CNTs (CNT-COOHs). Combination of IL and SANm-g-CNTs increase in to orders of magnitude SAN membrane tensile stress and modulus. Electrical conductivity of obtained membranes achieved the level of semi-conductor materials.